LEARNING ENGLISH LANGUAGE THROUGH LITERATURE AT UNIVERSITY LEVEL IN PAKISTAN - Khushboo Kainat; Dr. Saiqa Saddiq; Dr. Ehsan Ullah Danish; Dr. Wajid Riaz‡ (Journal of Religion and Society, 2024)
In the current research the researchers intake the notion of teaching English language through literature as many teachers think that the main goal of teaching English as a L2 (English as second language) or Foreign Language (EFL) is to help students interact smoothly. Because of this, they believe that L2 classes should only focus on learning language rules and structures. Recent trends in teaching English as a second Language (L2) show that including literature is important because it offers a real example of how language is used. Short stories are a great choice because they can assist students to make effective their different linguistics skills such as writing, reading, speaking and listening skills. The interesting nature of stories keeps students motivated to learn. This piece aims to help English as second Language (L2) teachers in Pakistani context to understand how useful short stories can be in their teaching. After explaining how to choose a short story, the focus shifts to ways to use the story to improve students' learning. The research is an experimental in nature selected university level students (14 years level) whereas 100 students each in each group (A & B) that have been experimented as procedure of research; Pre-Test and Post-Test, resulted that teaching English language can be imparted through literature and highly suggestive in Pakistani context. Keywords: L2 learning, English Language, Literature, Short stories, university level